Detection of T cells that secrete molecules which share determinants with antigen-specific T-cell factors. - Cleveland, W L (1981)
A single-cell secretion assay was used to detect cells that secrete products which react with an antiserum that binds T cell antigen-binding polypeptides. The antiserum (R11), which was produced by immunization of rabbits with a murine trinitrophenyl-specific suppressor factor, reacts with T cells and their products and with a suppressor T-cell clone but not with B cells or their products. The secretory cells this antiserum detected were found to be unevenly distributed among various organs (spleen, lymph node, and thymus) and, to different degrees, in spleens of various strains of mice. In unimmunized CBA/J mice, approximately 1-3% of spleen cells secreted macromolecules precipitable by R11. The majority of the secretory cells could be removed by panning with a mixture of Ly 1 and Ly 2 antibodies but not with either antibody alone. This is consistent with the cells having low surface antigen densities as a result of being either "pre-T" cells or mature secretory cells analogous to B-lineage plasma cells. In agreement with the latter possibility was our finding that the secretory activity of cells detected with antisuppressor factor was comparable to that of Ig-secretory cells as detected with an anti-Ig antiserum. However, higher numbers of R11+ secretory cells were seen in the immunoglobulin-negative fraction of spleen cells from nude mice, which could be interpreted to favor the first possibility. In either case this study shows that the single-cell assay technique is well suited for the detection and characterization of molecules released by immunoregulatory T cells.